2001
DOI: 10.1063/1.1406148
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency solid-state photovoltaic device due to inhibition of interface charge recombination

Abstract: The performance of solid-state dye-sensitized solar cells based on spiro-MeOTAD was considerably improved by controlling charge recombination across the interface of the heterojunction. This was achieved by blending the hole conductor matrix with a combination of 4-tert-butylpyridine (tBP) and Li[CF3SO2]2N. Open circuit voltages Uoc over 900 mV and short circuit currents Isc up to 5.1 mA were obtained, yielding an overall efficiency of 2.56% at AM1.5 illumination. These values have been fully confirmed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
383
0
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 495 publications
(407 citation statements)
references
References 11 publications
11
383
0
8
Order By: Relevance
“…These additives serve to control the doping level of the spiro-OMeTAD and also to enhance conductivity as well as overall cell performance. 29 The hole conductor solution was drop-cast onto the dye-sensitized TiO 2 films and allowed to infiltrate the pores before spin-casting at 1800 and 260 rpm/s acceleration for 40 s. Excess solution was carefully wiped with toluene and the films were dried overnight in a vacuum oven at 55°C. A 50 nm gold electrode was then thermally evaporated under high vacuum (10 -6 Torr) at <0.2 Å/s to complete the cell.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These additives serve to control the doping level of the spiro-OMeTAD and also to enhance conductivity as well as overall cell performance. 29 The hole conductor solution was drop-cast onto the dye-sensitized TiO 2 films and allowed to infiltrate the pores before spin-casting at 1800 and 260 rpm/s acceleration for 40 s. Excess solution was carefully wiped with toluene and the films were dried overnight in a vacuum oven at 55°C. A 50 nm gold electrode was then thermally evaporated under high vacuum (10 -6 Torr) at <0.2 Å/s to complete the cell.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…4,5 Several options are being investigated to substitute the organic solvent-containing electrolyte by a solid or low volatility phase. [6][7][8][9][10] In this respect, recent works on the use of room-temperature ionic liquids (RTILs) for dye-sensitized solar cells (DSCs) is particularly relevant. [11][12][13] RTILs are promising for many electrochemical systems such as actuators, batteries, supercapacitors, electrochromic windows, displays, photovoltaic cells, and light-emitting electrochemical cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, they still contain volatile components. It has been reported that the viscosity of imidazolium salts decreased and the photovoltaic performance increased when more than 0.5 M iodine was added to the molten salt [14][15][16]. Addition of a large amount of iodine increased the short circuit current but decreased the open circuit voltage because of the increase in dark current.…”
Section: Methodsmentioning
confidence: 99%